Definition of medical error and physicians' interest in changes in the law - Renata Husarz; Anna Jurek; Janusz Jaroszyński; Marzena Furtak-Niczyporuk; Aneta Mela (Kazimierz Wielki University, 2018)
The main purpose of the paper is to discuss the definition of medical error. Moreover, the statistical analysis was aimed at demonstrating at what level is the legal knowledge of the professional group of doctors, in relation to the performed profession. The research group consisted of doctors of different specializations, of different ages, with diverse work experiences, performing their profession in the Lubelskie voivodeship. These were people working on the basis of contract of employment, civil law contracts or individual medical practice, employed in provincial hospitals, clinics, district hospitals, outpatient's clinics, ambulances or medical centers. The author's questionnaire survey consisted of questions and answers for 298 doctors. Damage resulting from a widely understood medical error can be caused not only by the physician but by all medical staff or due to the organizational failure of the medical establishment. It must be stated with all conviction that the formulation of the concept of medical error is still ongoing and will evolve with the development of medicine as well as the law, which will strive to delineate the framework of its occurrence. The majority of doubts, which results from the obtained research, raises the issue of provision of medical help without the consent of the patient and the right to refuse treatment, but above all, what is quite surprising is the question of accepting gifts from pharmaceutical companies. The most frequently cited reasons influencing the lack of updating legal knowledge in the field of the performed profession were lack of time and a large number of duties, whereas the research group, in order to deepen their knowledge on that matter, most frequently used the Internet resources, industry articles, and on the third place was the training related to the subject matter of the medical law.